POTENTIAL OF INCOME INCREASE OBTAINED FROM VISITORS’ PERCEPTION AND BEHAVIOUR TOWARDS SERULINGMAS WILDLIFE RECREATION PARK BANJARNEGARA - Wibiyanto Setiawan; Tutut Sunarminto; Burhanuddin Masyud (Media Konservasi, 2021)
The needs for a large amount of fund demand the conservation agency to be more creative and able to compromise the visitors` necessities as an effort to guarantee wildlife welfare by providing suitable environment and its infrastructure. The objective of this study is to obtain the data and information related to the potential of income increase gained from the visitors’ perception and behavior towards Serulingmas Wildlife Recreation Park (TRM) in order to optimize many resources owned through tourism service innovations offered to visitors. The data were collected by delivering questionnaires to 150 visitors. The data collected included characteristics, motivations, and perceptions of visitors toward animal collection which were categorized into four, i.e.knowledge about animal, visitor behavior towards animals, collection rating, and animals` condition. Moreover, the condition of facilities in Serulingmas TRM was also evaluated. Furthermore, the management will be able to find the recent condition of collection animals based on the current information obtained from visitors. Thus, the information could be used to improve the management and increase the attractiveness about the animals for visitors. The results showed that seeing animals was the most popular activity for visitors and tiger was the favorite animal selected by the visitors of Serulingmas TRM. Visitors had a perception that the existence of Serulingmas TRM could increase knowledge and positive behaviors towards animals supported by a good and attractive cage arrangement, healthy animal condition, good facilities and service condition. Moreover, the visitor's interest in seeing animals along with the willingness of visitors to pay the entrance fee by adding the animal attraction could increase the income estimation by 36.67% started from 2019 only if the management increased the entrance fee to Rp25,000.00 (based on visitors` Willingness to Pay value). The improvement of attraction that pays attention on the visitors` desire and needs by also considering animals` welfare can support a sustainable conservation agency. Key words: ex situ conservation, Serulingmas Wildlife Recreation Park Banjarnegara visitors` perception, willingness to pay